PATRIOT GAMES: The (not so very) strange case of David Gibbs - Petrović, Новица (Наслеђе, 2012)
American national identity has been significantly influenced by the terrorist attacks of September 11th 2001 and their repercussions. In times of crises, when the very survival of a nation may be threatened, it is only natural for the nation in question to react by closing its ranks and manifesting an increased patriotism quotient. Often enough, the said patriotism boils down to mere token gestures, the purpose of which is twofold: to manifest one’s belonging to the given nation and contribute to the spirit of national unity. This paper analyzes such manifestations of patriotism drawing parallels with events and manifestations of national unity in the author’s own country.